Rancang Bangun Sistem Pemantauan Dan Kontrol Kualitas Udara Dalam Ruangan Berbasis Iot - Fredy Agung Dwi Cahyono; Denny Irawan (STEKOM PRESS, 2024)
Indoor air quality plays a vital role in public health, especially since people spend about 90% of their time indoors. Poor indoor air quality, often caused by chemical, physical, and biological pollutants, can severely impact health, comfort, and productivity. To tackle this issue, a robust air quality monitoring and control system was designed, featuring an ESP32 microcontroller paired with sensors such as the GP2Y1010AU0F dust sensor, MQ-7 carbon monoxide sensor, and MQ-2 smoke sensor, along with a fan to enhance air circulation. This system is capable of detecting air quality issues and taking corrective action. The ESP32 module, integrated with the Internet of Things (IoT) technology, enables real-time transmission of sensor data to a web server for continuous monitoring and prompt response. Researchers have made significant progress in creating an effective, system-based solution to improve and maintain indoor air quality